(untitled) (Kinesiology, 2018)
The aim of this study was to investigate the effects of small-sided game training (SSGT) versus conventional aerobic interval training (CAIT) on soccer-specific endurance performance, lactate threshold levels (mmol·L-1), short-passing ability and defensive and offensive skills of a soccer match. Before and after a 6-week training intervention period, eighteen amateur soccer players (age 21.8±4.8 years) were tested. The tests included the anaerobic threshold (AnT) test, the Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1), and the Loughborough Soccer Passing Test (LSPT). A manual notational match analysis system was utilized to evaluate the defensive and offensive skills of players during the matches. Both the SSGT and CAIT were performed two days a week and consisted of five sets of 6-minute periods of work at the individualized exercise intensity corresponding to the individual anaerobic threshold, with 3-minute of recovery periods between sets. Mann-Whitney U and Wilcoxon signed rank tests were used to examine the between- and within-group differences, respectively. Statistical analyses revealed that the SSGT group players exhibited significantly better in terms of the LSPT scores (p<.01) and the number of defensive and offensive skills (p<.05). However, no other significant differences in the other variables were observed (p>.05). The results of the study suggested that SSGT improved short-passing ability, various soccer skills and physiological parameters, while CAIT only improved physiological parameters. SSGT improves soccer-specific endurance and technical ability of players at the same time, meaning it is a time efficient way of training. Key words: small-sided game, anaerobic threshold training, soccer skills, short-passing ability